Parental Rejection and Emotional Reactivity: The Mediating Role of Self-Esteem - Viteri, Camila; Chen, Liang (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the relationship between perceived parental rejection and emotional reactivity among adolescents, with self-esteem as a potential mediating variable.Methods and Materials: A descriptive correlational design was used, involving 600 adolescents aged 15 to 18 years from urban areas in China, selected through multi-stage cluster sampling based on the Morgan and Krejcie table. Standardized self-report instruments were employed: the Parental Acceptance-Rejection Questionnaire (PARQ), the Rosenberg Self-Esteem Scale (RSES), and the Emotional Reactivity Scale (ERS). Data analysis was conducted using SPSS-27 for descriptive and inferential statistics and AMOS-21 for Structural Equation Modeling (SEM). The assumptions of normality, linearity, multicollinearity, and homoscedasticity were tested and confirmed.Findings: Pearson correlation analysis revealed significant relationships among the variables: parental rejection was positively correlated with emotional reactivity (r = .52, p < .001) and negatively with self-esteem (r = –.49, p < .001), while self-esteem was negatively correlated with emotional reactivity (r = –.55, p < .001). The SEM model showed acceptable fit indices (χ²/df = 2.53, GFI = 0.94, CFI = 0.96, RMSEA = 0.048). Path analysis indicated that parental rejection had a significant direct effect on self-esteem (β = –0.49, p < .001) and emotional reactivity (β = 0.30, p < .001). Self-esteem significantly predicted emotional reactivity (β = –0.55, p < .001), and a significant indirect effect of parental rejection on emotional reactivity through self-esteem was observed (β = 0.27, p < .001).Conclusion: The findings support a partial mediation model, indicating that self-esteem serves as a significant mechanism through which parental rejection influences adolescents’ emotional reactivity. These results highlight the importance of promoting positive parental behaviors and enhancing adolescent self-esteem to reduce emotional vulnerability.